การจำลองการถ่ายโอนความร้อนในไรเซอร์ของเตาเผาฟลูอิไดซ์เบดแบบหมุนเวียน - นพพล มังกรานนท์ชัย (จุฬาลงกรณ์มหาวิทยาลัย, 2004)
A circulating fluidized bed combustor (CFBC) has been widely used since it has high efficiency and can handle various kinds of fuels such as coal, biomass, or mixed feed. To improve its operation, the understanding of the hydrodynamics and heat transfer inside the unit is very important. This study was focused on heat transfer in the riser. A model was developed and simulated its hydrodynamics and heat transfer in the riser of a CFBC by using CFD simulator, fluent. Solid mass flux, gas velocity and top-end design were changed to observe the response in the riser. It also studied the effect ofthe top-end design on heat transfer coefficient. It was found that the design of the top-end had affected the solid circulation and solid density in the riser. The increase insolid density has increased the heat transfer coefficient.